Análisis para la instalación e implementación de un sistema de video y vigilancia "barrio seguro", como estrategia para reducir los índices delincuenciales por parte del gobierno autónomo descentralizado municipal de Babahoyo. - Andrade Pérez, Rodrigo Paul (2022)
The project for the installation and implementation of a "safe neighborhood" video and surveillance system, as a strategy to reduce crime rates, developed by the Municipal Autonomous Decentralized Government of Babahoyo, emerges as a tactic to mitigate the high crime rate that occurs in the city, which consists of the installation of video surveillance cameras and siren buttons, associated with an application installed on the cell phones of the members of a neighborhood, these devices are installed in different areas of the city, both urban and rural, where through a study by the Department of Citizen Security in coordination with the National Police, they determine the strategic areas for its implementation. After a community assembly where the parameters and co-responsibility of the neighborhood community are indicated through real-time monitoring in the installation of these devices, the cameras and siren buttons are installed by the technical staff of the Autonomous Decentralized Municipal Government of Babahoyo.The video surveillance cameras have infrared, movement alerts, a 270-degree pan around, coupled to a sound alert system (siren button), this entire system will be connected to the nearest UPC in order to have a immediate response time to the occasioned emergency. The Municipal authority seeks with this strategy to reduce the perception of insecurity and the crimes with the highest incidence in the sectors with the highest criminal risk. To contribute to the strengthening of security in the canton of Babahoyo and reverse the growing trend of the criminal boom; situation that is possible to achieve in coordination between citizens, National Police and Municipal Government.